e-Prescription: An e-Health System for Preventing Adverse Drug Events in Community Healthcare - Irma M. Puspitasari; Soegijardjo Soegijoko (Universitas Padjadjaran, 2012)
The paper describes development activities of an e-health system for community health center (Puskesmas) with integrated adverse drug events e-prescription module, consist of system design and development, human resource development, e-health system realization, laboratory and implementation test of e-health system. Some e-readiness evaluations were conducted, through a number of field visits and questionnaires. The results had been used in the e-health system design and development, installation of the internet access infrastructure, and implementation of the education and hands-on training for the medical and administrative staff of the healthcare units. After completing the e-health system design and development as well as system realization and laboratory tests stages, a series of field implementation and experiments have been successfully conducted at Puskesmas Babakansari in Bandung. A number of users feed back have been obtained and used for further improvements on both of the software and hardware modules. The e-health system with integrated e-prescription module has successfully developed and shown its expected functions in: patient registration, medical record, paperless prescription, producing the required reports and preventing possible adverse drug events.Key words: Adverse drug events, community health center, e-health, e-prescription e-Prescription: Sistem e-Health untuk Pencegahan Adverese Drug Event di PuskesmasAbstrakArtikel ini mendeskripsikan pengembangan sistem e-health untuk puskesmas dengan modul e-prescription yang terintegrasi adverse drug event. Modul ini terdiri dari desain sistem dan pengembangan, pengembangan sumber daya manusia, realisasi sistem e-health, laboratorium dan tes implementasi sistem e-health. Beberapa evaluasi kesiapan penggunaan elektronik (e-readiness) dilakukan melalui kunjungan lapangan dan kuesioner. Hasil evaluasi digunakan dalam desain dan pengembangan sistem e-health, instalasi akses internet, implementasi pendidikan dan pelatihan bagi staf medis dan administrasi. Setelah sistem e-health selesai dan dikembangkan sesuai dengan realisasi dan tahapan tes laboratorium, sejumlah implementasi dan eksperimen telah sukses dilakukan di Puskesmas Babakansari di Bandung. Respon yang diperoleh digunakan untuk pengembangan modul lebih lanjut dari segi software dan hardware. Sistem e-health yang terintegrasi dengan modul telah sukses dikembangkan sesuai dengan fungsi yang diharapkan: registrasi pasien, medical record, resep tanpa kertas, pelaporan dan pencegahan kemungkinan adverse drug events.Kata kunci: Adverse drug events, pusat kesehatan masyarakat, e-health, e-prescription